“Spider Web”-like zonular deposits in pseudoexfoliation syndrome: endoscopic insights—a case report - Lin, Bin; Zhang, Ling; Li, Dong-kan (Frontiers in Medicine, 2025)
Pseudoexfoliation syndrome (PEX) is a systemic fibroproteinopathy with limited global epidemiological data and unclear pathogenesis. This case report describes a 70-year-old Asian woman presenting with left eye soreness and blurred vision. She was diagnosed with PEX based on typical ocular characteristics, including grayish-white debris on the pupillary margin, pigment residues in the anterior chamber angle, and annular opacity around the anterior lens capsule after pupil dilation. During surgery, endoscopic observation revealed extensive grayish-white flocculent deposits covering the entire circumference of the zonules, resembling a spider web—findings consistent with the “fibrin-like deposits” described in autopsy studies. Such exfoliated material may damage the intraocular environment through mechanical damage and chronic inflammatory responses. This is supported by intraoperative anterior chamber depth instability and a markedly elevated interleukin-8 (IL-8) concentration (557.3 pg/mL) in the anterior chamber fluid. This case provides in vivo visualization of zonular abnormalities in a living Asian PEX patient using endoscopic technology, offering insights that extend beyond the capabilities of traditional imaging. It contributes direct evidence to enhance understanding of the pathogenesis of PEX-related glaucoma and suggests that intraoperative endoscopic assessment may serve as a valuable tool for evaluating zonular integrity and intraocular inflammation in PEX patients. Future integration of artificial intelligence-based image analysis, combined with intraocular fluid inflammatory marker assessment, may enable quantification of deposit parameters and establishment of a zonular lesion grading system, potentially optimizing PEX management.